The Effect of Financial Literacy, Income, Financial Self-Efficacy, and Locus of Control on the Financial Management - Muhammad Zidan Faqihuddin; Betanika Nila Nirbita (Universitas Negeri Semarang, 2025)
This study aims to determine the influence of financial literacy, income, financial self-efficacy and locus of control on students' financial management behavior. This study uses a quantitative method. The population used in this study were students of the Accounting Study Program, Faculty of Vocational Studies, Yogyakarta State University. Sampling was carried out using a purposive sampling technique of 100 respondents. The data collection method used a questionnaire distributed online. This study uses multiple linear regression analysis techniques with SPSS 26 software. The results of the study show that (1) Financial literacy has a significance value of 0.000 < 0.05, which means that financial literacy has a positive effect on students' financial management behavior. (2) Income has a significance value of 0.031 < 0.05, which means that income has a positive effect on students' financial management behavior. (3) Financial self-efficacy has a significance value of 0.000 < 0.05, which means that financial self-efficacy has a positive effect on students' financial management behavior. (4) Locus of control has a significance value of 0.022 < 0.05, which means that locus of control has a positive effect on students' financial management behavior.